2021
DOI: 10.1111/jfr3.12742
|View full text |Cite
|
Sign up to set email alerts
|

Identifying tree characteristics to determine the blocking effects of water conveyance for natural flood management in urban rivers

Abstract: Plants, especially trees, provide ecological functions but may harm the flood conveyance efficiency of rivers. Understanding the impacts of tree heights, tree areas, and tree locations on flood levels is crucial for floodplain management. This study aims to present a methodology to improve the performance of hydrodynamic modeling by considering plant resistance with the goal of analyzing flood risk reduction strategies that support ecological conservation enhancement. An unmanned aerial vehicle was used to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Along banks, vegetation can influence bank stability and channel morphology [29,30], whereas, on the floodplain, plants increase the roughness, resulting in accelerated sedimentation [31,32] and increased flood levels [33][34][35]. Therefore, it is highly important to understand the physical and biological structure of riparian vegetation and to model the hydrological consequences of its alteration [36][37][38]. Applying this knowledge to riparian vegetation maintenance (e.g., forestry, invasive species clearance) vegetation management could be sustainable from the perspectives of ecology and flood control [23,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Along banks, vegetation can influence bank stability and channel morphology [29,30], whereas, on the floodplain, plants increase the roughness, resulting in accelerated sedimentation [31,32] and increased flood levels [33][34][35]. Therefore, it is highly important to understand the physical and biological structure of riparian vegetation and to model the hydrological consequences of its alteration [36][37][38]. Applying this knowledge to riparian vegetation maintenance (e.g., forestry, invasive species clearance) vegetation management could be sustainable from the perspectives of ecology and flood control [23,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The important hydraulic engineering task of assessing flood capacity is based primarily on cross-sectional area changes and flow resistance factors (Shih & Chen 2021). In recent studies (e.g., Dimitriadis et al 2016), researchers demonstrated through benchmark simulations that the variability and uncertainty of flood propagation are primarily caused by channel geometry and roughness as compared to other factors such as inflow, longitudinal gradient, floodplain roughness, and model structure.…”
Section: Introductionmentioning
confidence: 99%